Potential Oxidative Treatment Using Pb-PbO2 Electrode in Electrodecolorizing Batik Wastewater - Didik Setiyo Widodo; Rahmad Nuryanto; Abdul Haris; Prihastuti Santini Laksmi Dewi; Lutfia Apipah (Jurnal Kimia Sains dan Aplikasi, 2018)
Electrodecolorization of batik wastewater has been done. Study was performed to remediate aquatic environment containing dyes of batik industry by electrolysis, decreasing COD and some metal ions as well. Research was conducted by electrolyzing sample from Buaran Pekalongan and Semarang using Pb and PbO2 as electrodes at a constant applied potential. Solution after treating were analysed, zeolite sieving treatment, and final analysis by UV-Vis spectrophotometer for measuring decolorization percentages, atomic absorption spectrophotometerer (AAS) for evaluating metal ions of Cu2+, total Fe and Na+, and COD analysis. Results show that electrolysis of batik wastewater using PbO2 as anode effectively decolorize and decreasing COD values. Sample containing indigozol and remazol black B (RBB) were decolorized up to 100%. CODs were reduced to 98.6% and 95.4%, respectively. Zeolite treatment enhancing water quality by reducing ion concentration of Cu2+, total Fe ions and Na+.